Digital Transformation Risk Management in Credit Channeling - Adelya Hidayati; Purwatiningsih Lisdiono (AFRE (Accounting and Financial Review), 2024)
This study aims to evaluate the implementation of credit risk management at Bank XYZ in the context of providing credit through channeling cooperation with P2P platforms. Using a qualitative research method with a case study approach, the study involves senior employees and key officials of Bank XYZ directly involved in credit risk management practices, as well as partner institutions. Data collection is conducted through document analysis and interviews, utilizing primary and secondary data. The findings reveal that while Bank XYZ has successfully integrated digital technology to streamline its credit provision processes, significant challenges remain in managing credit risk due to borrower defaults, ensuring data security, and maintaining regulatory compliance. Although comprehensive risk identification processes, strict data security policies, and robust access controls are in place, improvements are needed in updating risk analysis procedures and regularly reassessing risk appetite and tolerance. This research provides valuable insights for companies to enhance their credit risk management practices and for regulators to formulate appropriate policies for the fintech industry. Supported by the ISO 31000 framework, the study aims to enhance the robustness of risk management practices at Bank XYZ, aligning them with international best practices in risk management.DOI: https://doi.org/10.26905/afr.v7i1.10334Â Â Â